2011
DOI: 10.1016/j.taap.2009.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts on oxidative/carbonyl stress, inflammation and epigenetics in pathogenesis of chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a global health problem, and current therapy for COPD is poorly effective and the mainstays of pharmacotherapy are bronchodilators. A better understanding of the pathobiology of COPD is critical for the development of novel therapies. In the present review, we have discussed the roles of oxidative/aldehyde stress, inflammation/immunity, and chromatin remodeling in the pathogenesis of COPD. Imbalance of oxidant/antioxidant balance caused by cigarette smoke and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
207
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(211 citation statements)
references
References 224 publications
1
207
0
2
Order By: Relevance
“…However, most studies have attributed such CS-induced oxidative damage mainly to the endogenous RNS/ROS generated in the lung during smoking (18-20, 34, 37, 38) without analyzing the comparative role of oxidants furnished by the CS itself in such damage process. Although several mechanisms associating oxidative damage of the lung to the pathogenesis of CS-induced emphysema has emerged over the years, none have conjointly addressed the role of CS oxidants along with the lung-generated oxido-nitrosants in the disease process (23,38,39). Indeed, our present work reveals the thus far unanalyzed diverse share and comparative role of the CS oxidants and cellular oxido-nitrosants in emphysematous lung damage inflicted by CS.…”
Section: Discussionmentioning
confidence: 78%
“…However, most studies have attributed such CS-induced oxidative damage mainly to the endogenous RNS/ROS generated in the lung during smoking (18-20, 34, 37, 38) without analyzing the comparative role of oxidants furnished by the CS itself in such damage process. Although several mechanisms associating oxidative damage of the lung to the pathogenesis of CS-induced emphysema has emerged over the years, none have conjointly addressed the role of CS oxidants along with the lung-generated oxido-nitrosants in the disease process (23,38,39). Indeed, our present work reveals the thus far unanalyzed diverse share and comparative role of the CS oxidants and cellular oxido-nitrosants in emphysematous lung damage inflicted by CS.…”
Section: Discussionmentioning
confidence: 78%
“…It is shown that NF-jB-induced acetylation of histone H3, but not histone H2A, H2B, or H3, occurs in epithelial cells on specific lysine residues (Lys8 and Lys12) at NF-jB-responsive regulatory elements on proinflammatory genes (57). Oxidative stress and CS activate NF-jB, HAT, CBP/p300 leading to specific histone acetylation in macrophages and lung cells (60,93,178,179,187). Therefore, development of small molecules that target for inhibition of HATs (e.g., CBP/p300, PCAF, and GCN) may be useful for therapeutic intervention in COPD and other chronic inflammatory lung diseases associated with smoking mediated oxidative stress (8,99).…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%
“…Повышение концентрации NO в выдыхаемом воздухе характерно только для периода обострения ХОБЛ [63]. У больных ХОБЛ (особенно куриль-щиков) характерно наличие высоких уровней кон-центрации пероксинитрита (ONOO -), нитрованых белков (фибриноген, трансферрин, плазминоген, церулоплазмин) [49].…”
Section: хроническая обструктивная болезнь легкихunclassified